The hypothenuse is the opposite side of the right angle
so that means that in this triangle the hypotenuse is 7
Answer:
x=2
Step-by-step explanation:
5(6x-1)-10x+5=4(x+10)-4x
simplify both sides
30x-5-10x+5=4x+40-4x
Simplify even further
20x=40
x=2
Answer:
mtx(8x+3)-3mt(8x+3)
)Step-by-step explanation:
Answer:
0
Step-by-step explanation:
Multiplying the first equation by xy, we have ...
x^2 +y^2 = -xy
Factoring the expression of interest, we have ...
x^3 -y^3 = (x -y)(x^2 +xy +y^2)
Substituting for xy using the first expression we found, this is ...
x^3 -y^3 = (x -y)(x^2 -(x^2 +y^2) +y^2) = (x -y)(0) = 0
The value of x^3 -y^3 is 0.
Answer:
-11
Step-by-step explanation:
Solve using linear equation
-12x=-8+116
-12x=108
-x=11
x=-11